FAIR TRADE : MENUJU SEBUAH SISTEM PERDAGANGAN (BARU) BAGI NEGARA-NEGARA DI DUNIA - Wahid Noor Jayn (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2019)
As one of the ancient practices that are still ongoing to date, trade becomes a thing that goes hand in hand with human civilization. The meeting of interests between the seller and the buyer, the producer and the consumer is absolute by the principle of mutual benefit. Current inter-state trade practices are often considered to be detrimental to the Southern states. Supposedly, modernity and the advancement of science and technology make trade principles run in harmony and balance among stakeholders. Developed countries, geographically located in the Northern region, have reliable human resources. It is also supported by a strong financial and governance system. Nevertheless, Northern countries have limited natural resources. On the other hand, the Southern states are endowed with abundant natural wealth but have limitations in human resources. Essentially these two extremes can harmonize. Developed countries are criticized for playing a dual role in implementing their trade policies. In addressing these issues, Fair Trade as a social movement provides hope for the realization of trade justice and provides assurance for producers who come from developing countries in order to get a decent and sustainable life